Mineral Nutrition Contributes to Plant Disease and Pest Resistance - Timothy M. Spann; Arnold W. Schumann (EDIS, 2010)
HS1181, a 5-page illustrated fact sheet by Timothy M. Spann and Arnold W. Schumann, provides a summary of plant mineral nutrition, discussing how nutrient levels may affect plant growth and potential susceptibility to plant diseases and pests. Published by the UF Department of Horticultural Sciences, July 2010.